KEBIJAKAN HUKUM PIDANA TERHADAP PERILAKU PENGUSAHA DALAM PRODUKSI, PENYIMPANAN DAN PENJUALAN OBAT-OBATAN TANPA KEAHLIAN DAN KEWENANGAN - WIDIARTO PURWOTO, EKO, SOPONYONO (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The circulation of Counterfeit medicines more increase, it’s be influence Pharmacy industry and Producer too. The composition in the market can be harmfully because of Many consumed, include generic and counterfeit The recht staat Policies research in producer behavior to produce, warehouse and sell of medicine without expert and authority have 2 problems: Criminal Law Policies in restrict the producer behavior to produce, warehouse and sell of medicine without expert and authority at present? Criminal Law Policies in restrict the producer behavior to produce, warehouse and sell of medicine without expert and authority at the next? Writer do researching with Empiric juridical approach methode, Empiric yuridis approach method is procedures to solve problem with second information, Primary information in the fact, dan Task of Badan POM in protect Consumer medicine product is law in action and the effects of changes producer can be restrict abuse of consumer law ( Nomor 8 Tahun 1999) Can be Concluded as Criminal Law Policy into the producer behavior to produce, warehouse and sell of medicine without expert and authority can be feel Ineffective becaus imprisonment sentenced. Make less with the applied Criminal Law Policies of producer behavior can round up who ‘s product as in law the code of conducts as the rules